2011
DOI: 10.1002/etc.570
|View full text |Cite
|
Sign up to set email alerts
|

PBDE developmental effects on embryonic zebrafish

Abstract: Polybrominated diphenyl ethers (PBDEs) have become ubiquitous environmental contaminants with potential for bioaccumulation and maternal-fetal transfer that has led to regulatory bans and/or phasing out of several technical mixtures of PBDEs. In the present study, six PBDE congeners (BDE 28, BDE 47, BDE 99, BDE 100, BDE 153, BDE 183) were evaluated for developmental effects on embryonic zebrafish. These congeners were chosen because they are environmentally relevant and cover a wide range of physical-chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 37 publications
(30 reference statements)
9
73
3
Order By: Relevance
“…PBDEs can cause neurobehavioral alterations in rodent models (Eriksson et al, 2002;Kodavanti et al, 2010). Recently, locomotor behavior was used as an approach to study the neurobehavioral effects of PBDEs in zebrafish (Chen et al, 2012b;Chou et al, 2010;He et al, 2011;Usenko et al, 2011). Our study confirmed that BDE-209 in the presence of nano-TiO 2 induced neurotoxicity in zebrafish.…”
Section: Discussionsupporting
confidence: 80%
“…PBDEs can cause neurobehavioral alterations in rodent models (Eriksson et al, 2002;Kodavanti et al, 2010). Recently, locomotor behavior was used as an approach to study the neurobehavioral effects of PBDEs in zebrafish (Chen et al, 2012b;Chou et al, 2010;He et al, 2011;Usenko et al, 2011). Our study confirmed that BDE-209 in the presence of nano-TiO 2 induced neurotoxicity in zebrafish.…”
Section: Discussionsupporting
confidence: 80%
“…Alterations in neurobehavioral performance have also been reported for killifish (Fundulus heteroclitus) embryos exposed to DE-71 [20]. Recently, behavioral studies have been carried out to examine the neurobehavioral effects of PBDEs in zebrafish [21][22][23]. These studies indicated that behavioral measurement is a sensitive indicator of PBDE-induced neurotoxicity.…”
Section: Introductionmentioning
confidence: 89%
“…48,49 Recently, locomotor behavior approaches have also been performed to study the neurobehavioral effects of PBDEs in zebrafish. 29,50 Neurobehavior is an integrated response of many physiological and biochemical processes. Thus, alternations of locomotor behavior could be due to downregulation of AChE gene transcription, the inhibition of AChE activity, alterations of the natural function of genes and proteins, or by direct neurotoxic effects on neuronal cells.…”
Section: Environmental Science and Technologymentioning
confidence: 99%